Bringing all the baggage together: Teaching history with a new paradigm - Burenheide, Bradley (My University, 2011)
This article proposes a new paradigm for the implementation of historical thought and historical inquiry into classroom teaching. Where most of the teaching in advanced level classes centers upon teaching content at the historical macrostructure level, the authors suggest that much is to be gained from exploring the discipline of history at the levels of the historical microstructure and individual consciousness. Each of these cultural levels is defined and an example of its use in the classroom is provided with a concluding discussion of the implications of this paradigm and the potential it holds. This paper served as a foundational paper for future research and serves the purpose of a “white paper” in the field of history education.
Keywords: History teaching; Historical inquiry; Historical thought; Curriculum models